KERAGAAN TINGKAT PENGETAHUAN, PERSEPSI DAN RESPON PESERTA TEMU TEKNIS PENELITI-PENYULUH BALITBANGTAN DAN PENYULUH JAWA TENGAH - Hidayah, Restu; Lestari, Fitri; Fatmawati, Nurul Laela; Kushartanti, Ekaningtyas (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2021)
The technical meeting for Researcher – Extension Workers aims to train the extension workers, who carry out the Specific Technology Adaptation 2020 in 12 districts in Central Java. In this technical meeting, several technological innovations of Balitbangtan were presented as alternative choices of technological innovations to be applied. Evaluation of technical meetings is an indicator of the success of an extension seen from the increase in knowledge, perceptions and responses of participants. The purpose of this paper is to identify the knowledge level of the participants, identify the perceptions, and also responses of participants. The observed parameters are the characteristics of the respondents, the level of knowledge, perceptions and responses of the respondents. Data was collected through survey by questionnaire and analyzed it with non-parametric analysis and descriptive. The study results that respondent’s knowledge increase 49,01%. Respondents give perceptions and responses on high-level of assessment for the benefit of technical meeting because it is very helpful to supporttheir main tasks and functions.